A nanostructured anti-biofilm surface widens the efficacy against spindle-shaped and chain-forming rod-like bacteria. Issue 36 (8th September 2020) - Li, Xin; Tsui, Kwong-Hoi; Tsoi, James K. H.; Green, David W.; Jin, Xiao-zhuang; Deng, Yong Qiang; Zhu, Yao Min; Li, Xu Guang; Fan, Zhiyong; Cheung, Gary Shun-pan
Abstract : Current control of pathogenic bacteria at all biomaterial interfaces is poorly attuned to a broad range of disease-causing pathogens. Abstract : Current control of pathogenic bacteria at all biomaterial interfaces is poorly attuned to a broad range of disease-causing pathogens. Leading antimicrobial surface functionalization strategies with antimicrobial peptides (AMPs), defensins, have not shown their promised efficacy. One of the main problems is the lack of stability and swift clearance from the surface. Surface nanotopography bearing sharp protrusions is a non-chemical solution that is intrinsically stable and long-lasting. Previously, the geometrically ordered arrays of nanotipped spines repelled or rapidly ruptured bacteria that come into contact. The killing properties so far work on cocci and rod-like bacteria, but there is no validation of the efficacy of protrusional surfaces on pathogenic bacteria with different sizes and morphologies, thus broadening the utility of such surfaces to cover increasingly more disease entities. Here, we report a synthetic analogue of nanotipped spines with a pyramidal shape that show great effectiveness on species of bacteria with strongly contrasting shapes and sizes. To highlight this phenomenon in the field of dental applications where selective bacterial control is vital to the clinical success of biomaterial functions, we modified the poly(methyl)-methacrylate (PMMA) texture and tested it against Streptococcus mutans, Enterococcus faecalis, Porphyromonas gingivalis, and Fusobacterium nucleatum . These nanopyramids performed effectively at levels well above those of normal and roughened PMMA biomaterials for dentistry and a model material for general use in medicine and disease transmission in hospital environments.